A Binary search algorithm: pencarian email berdasarkan nama menggunakan flowgorithm - Suherman, Sunandar (Maliki Interdisciplinary Journal, 2025)
Searching email by name is one of the tasks that is often done in email information systems. This task can be done with various algorithms, one of which is the binary search algorithm. The binary search algorithm is a search algorithm that works by repeatedly dividing the data set into two parts until the data being searched is found. In this study, the binary search algorithm is used to search for emails by name using Flowgorithm. Flowgorithm is a flowchart software that can be used to create algorithms visually. The results of the study show that the binary search algorithm can be used to search for emails by name efficiently. This algorithm can find the data being searched in a relatively short time, which is O(log n).